Manifestations of Public and Self-Stigma of Physical Disability: A Scoping Review in Rehabilitation and Disability Research. - Hyun-Ju Ju; Harley, Debra; Miller-Rankin, Jennifer (Journal of Applied Rehabilitation Counseling, 2023)
As physical disability exists globally and stigma is prevalent, the need for research on the stigma of physical disability is identified in the fields of rehabilitation and disability studies. This study conducted a scoping review for analyzing the manifestations of stigma on people with physical disabilities using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Search terms were used with three electronic databases (Pub-Med, ERIC, and Psyc-INFO) for peer-reviewed rehabilitation and disability journals published from 2000 to 2020 time frame. A total of 683 records were identified, of which 146 were duplication and 413 were excluded by title and abstract, and 124 full-text articles were assessed for eligibility. The final number included was 3 quantitative studies and 8 qualitative synthesis studies for a total of 11 studies. This study revealed that the stigma related to people with physical disabilities is a global issue, and stigma appeared in various settings of society (e.g., education, workplace, rehabilitation and sexual health care, and the benefit system). Public stigma usually appeared related to physical image and the presence of a wheelchair, and most of the studies related to self-stigma were in the stage of recognizing the public stigma, and there were also responses to the public stigma to aim for opportunities for coping and change. Awareness of stigma led to negative psychosocial well-being such as depression, self-efficacy, and quality of life. Future researchers should consider cultural differences and specific types of physical disabilities.